Preparation of silver nanoparticles impregnated in polymer membrane for water treatment - Au, Sabrina Kai Ting (2019)
Ballast water is used to stabilise the ships during voyages. A wide variety of foreign bacteria are introduced to non-native places by means of ballast water causing irreversible damages to the native ecosystem and bring about health diseases. Physical filtration system is used to prevent bacteria transfer but is prone to biofouling which greatly reduces the efficiency of the membrane. Silver nanoparticles are known for its anti-microbial properties and have been used in many application including water treatment and medical purposes and therefore it may be used in membranes to disinfect ballast water. This research discusses the antibacterial effect of silver nanoparticles enhanced ultrafiltration membranes on various bacteria and as well as seawater. Different concentrations of silver nitrate have been reduced using a reducing agent to achieve silver nanoparticles which was impregnated on a membrane and a novel pathway was created to immobilize the AgNPs on the membrane surface by interfacial polymerization. The anti-bacterial activity was investigated using the plate count method at fixed time interval. Results shows that the optimized antibacterial membrane with silver concentrations of 50 mmol/L and PEI concentration of 20 mmol/L are effective in obliterating gram-positive bacteria but less effective with gram-negative bacteria. As seawater comprises of both type of bacteria, it took a longer time to obliterate all the bacteria. Further investigations are carried out to for an extended period of time and results shows that the amount of silver ions released reduces greatly overtime and hence reducing the killing rate of the bacteria.